The effects of ibuprofen on delayed muscle soreness and muscular performance after eccentric exercise - Tokmakidis, S. P.; Kokkinidis, E. A.; Smilios, I.; Douda, H. (The Journal of Strength and Conditioning Research, 2003)
The purpose of this study was to examine the effects of ibuprofen on delayed onset muscle soreness (DOMS), indirect markers of muscle damage and muscular performance. Nineteen subjects (their mean [± SD] age, height, and weight was 24.6 ± 3.9 years, 176.2 ± 11.1 cm, 77.3 ± 18.7 kg) performed the eccentric leg curl exercise to induce muscle soreness in the hamstrings. Nine subjects took an ibuprofen pill of 400 mg every 8 hours within a period of 48 hours, whereas 10 subjects received a placebo randomly (double blind). White blood cells (WBCs) and creatine kinase (CK) were measured at pre-exercise, 4-6, 24, and 48 hours after exercise and maximal strength (1 repetition maximum). Vertical jump performance and knee flexion range of motion (ROM) were measured at pre-exercise, 24 and 48 hours after exercise. Muscle soreness increased (p < 0.05) in both groups after 24 and 48 hours, although the ibuprofen group yielded a significantly lower value (p < 0.05) after 24 hours. The WBC levels were significantly (p < 0.05) increased 4-6 hours postexercise in both groups with no significant difference (p > 0.05) between the 2 groups. The CK values increased (p < 0.05) in the placebo group at 24 and 48 hours postexercise, whereas no significant differences (p > 0.05) were observed in the ibuprofen group. The CK values of the ibuprofen group were lower (p < 0.05) after 48 hours compared with the placebo group. Maximal strength, vertical jump performance, and knee ROM decreased significantly (p < 0.05) after exercise and at 24 and 48 hours postexercise in both the placebo and the ibuprofen groups with no differences being observed (p > 0.05) between the 2 groups. The results of this study reveal that intake of ibuprofen can decrease muscle soreness induced after eccentric exercise but cannot assist in restoring muscle function.